Reinventing Local Community Wisdom through Educulturalism Methods as an Effort to Increase the Existence of Indonesian Economic Development - Fauzani; Putri Ratna Kencana; Sirajudin Al Aksari; Lakoni Pribadi Putra (Universitas Indo Global Mandiri, 2024)
Indonesia, which consists of ± 429 ethnic groups in the archipelago, has diverse local wisdom. Economic globalization is an inevitable reality in the world economic map in the 21st century. The problems in Indonesia related to economic globalization are the large amount of competition between modern markets as well as unemployment and poverty which ultimately cause inequality both in terms of social and economic growth. Territorial boundaries are no longer an obstacle to interacting with fellow humans. In addition, economic globalization will have a relationship that affects each other between various countries. The purpose of this study is to find out the role of local wisdom through the method of educulturalism in economic development, by analyzing and designing a model based on related literature studies. Several studies that have been carried out focus on economic development by prioritizing local wisdom in the local area. By using a qualitative method of descriptive approach based on reviews, theories and literature studies, it can be concluded that there are at least three types of local wisdom that are able to be a counterweight to global economic competition in an effort to carry out economic development. First, maintaining and utilizing the preservation of natural resources. Second, to function a creative economy based on local wisdom. Third, running a small business based on local wisdom. Thus, local wisdom is required to be a determining element for the success of community and natural resource development in realizing equitable economic development. Keywords: Local Wisdom, Educulturalism, Economic Globalization, Economic Development, Natural Resources